A case for considering age and sex when prescribing rest intervals in resistance training - Grgic, Jozo; Schoenfeld, Brad J. (Kinesiology, 2019)
Current resistance training position stands recommend that rest interval duration in resistance training should be prescribed based on the training goal and exercise selection. However, these recommendations are mostly extrapolated from studies that included young men as participants. Therefore, they cannot necessarily be generalized across all age groups and to all resistance training programs. Herein, two important factors that might be neglected in the current exercise prescription guidelines are discussed: (i) age of the individual, and (ii) gender. Older adults seem to require a shorter duration rest interval to achieve recovery between sets. Due to the differences in fatigability between genders, it can be speculated that men need a longer duration rest interval to maintain high levels of performance when compared to women. Both gender and age seem to be relevant variables when determining rest interval duration, and should not be overlooked by exercise practitioners in program design.